Learning Innovation Social Science in Elementary Schools in Dealing with the Society 5.0 Era - Alivia Ayusha Putri; Andiana Rachmawati; Esti Nurazizah; Fira Faizah Hidayatih; Gisca Olivia; Izam Rosidik (Balai Publikasi Indonesia, 2023)
The concept of the society 5.0 era is an era where humans are expected to be able to solve various problems and challenges by utilizing various innovations and centering on technology. Era society 5.0 is utilized as a humane way of improving the quality of life by developing scientific and technological innovations in various aspects of life. This research uses the library study method, namely a collection of related activities by collecting library data, reading, taking notes, and designing research materials. This study discusses how social studies learning innovations in elementary schools face the society 5.0 era. In this era, humans are expected to understand and master technology well. In addition, the era of Society 5.0 requires humans to be able to think more critically, creatively and wisely. In facing the Society 5.0 era, the government has asked many people to continue to develop themselves so they are not controlled by technology. Social studies learning towards society 5.0 must focus on developing students' intellectual, emotional, cultural, social skills, and learning skills, according to the characteristics of that era. In teaching students, teachers can innovatively, creatively and actively use a variety of learning-centered learning methods, strengthening information and communication technology learning and making an important contribution to improving the quality of learning, by always paying attention to the characteristics together.